2022
DOI: 10.1126/science.abn6583
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of CTCF- and cohesin-mediated chromatin looping revealed by live-cell imaging

Abstract: Animal genomes are folded into loops and topologically associating domains (TADs) by CTCF and loop extruding cohesins, but the live dynamics of loop formation and stability remain unknown. Here, we directly visualize chromatin looping at the Fbn2 TAD in mouse embryonic stem cells using super-resolution live-cell imaging and quantify looping dynamics by Bayesian inference. Unexpectedly, the Fbn2 loop is both rare and dynamic, with a looped fraction of ~3-6.5% and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
219
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(294 citation statements)
references
References 83 publications
39
219
2
Order By: Relevance
“…Thus, loop formation requires efficient cohesin loading onto chromatin, while its processivity is restricted by regulated "load-unload" cycles. However, recent live-cell imaging of the mouse Fbn2 locus showed that full looping is rarely achieved and that, most of the time, cohesin-extruded loops within an active domain form without bringing both CTCF boundaries together (Gabriele et al, 2022). This can be explained by the notion that 3D genome architecture results from the antagonistic interplay between loop extrusion and compartmentalization of homotypic (i.e., active-to-active or inactive-to-inactive) chromatin domains (Nuebler et al, 2018;Rada-Iglesias et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, loop formation requires efficient cohesin loading onto chromatin, while its processivity is restricted by regulated "load-unload" cycles. However, recent live-cell imaging of the mouse Fbn2 locus showed that full looping is rarely achieved and that, most of the time, cohesin-extruded loops within an active domain form without bringing both CTCF boundaries together (Gabriele et al, 2022). This can be explained by the notion that 3D genome architecture results from the antagonistic interplay between loop extrusion and compartmentalization of homotypic (i.e., active-to-active or inactive-to-inactive) chromatin domains (Nuebler et al, 2018;Rada-Iglesias et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, single-molecule experiments demonstrated that RNA polymerase (RNAP) can push a passively diffusing cohesin complex along DNA in vitro (41). However, it is not known how transcription-driven cohesin relocalization can be reconciled with now well established observations of active loop extrusion by cohesin (3)(4)(5)42), and what patterns of chromatin organization can emerge from transcription-extrusion interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is in a “partially extruded” state for ∼92% of the time. In such a state, ∼57–61% of the chromatin exists in ∼1–3 cohesin loops while the rest remain un-extruded [21] .…”
Section: Chromatin Hubs: the Biological Sidementioning
confidence: 99%